1998
DOI: 10.1097/00006454-199812000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Severity of respiratory syncytial virus disease related to type and genotype of virus and to cytokine values in nasopharyngeal secretions

Abstract: The severity of disease in patients admitted with acute RSV infections can be correlated to the RSV type as determined by PCR, to the RSV genotype as determined by nucleic acid restriction analysis and to the ratio IL-6:TNF-alpha in NPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
2
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 36 publications
8
73
2
6
Order By: Relevance
“…Comparable high amounts of TNF-α and IL-6, next to IL-1β and IL-8 have been found in nasal secretions and superficial mucosal biopsies in RSV-infected infants and children [80,91]. Further evidence for a role of TNF-α and IL-6 in acute RSV infections comes from a patient study in which higher IL-6: TNF-α ratios in nasopharyngeal secretions are correlated with the lower severities of the disease [61]. This finding can be explained by the negative effects of IL-6 on TNF-α and IL-1 release and resulting proinflammatory effects [110].…”
Section: Cytokines In Viral Respiratory Diseases Of Humansmentioning
confidence: 99%
“…Comparable high amounts of TNF-α and IL-6, next to IL-1β and IL-8 have been found in nasal secretions and superficial mucosal biopsies in RSV-infected infants and children [80,91]. Further evidence for a role of TNF-α and IL-6 in acute RSV infections comes from a patient study in which higher IL-6: TNF-α ratios in nasopharyngeal secretions are correlated with the lower severities of the disease [61]. This finding can be explained by the negative effects of IL-6 on TNF-α and IL-1 release and resulting proinflammatory effects [110].…”
Section: Cytokines In Viral Respiratory Diseases Of Humansmentioning
confidence: 99%
“…IL-17-producing T cells are induced in primary infections through pathways that involve STAT3 and IL-6 (16,17). High levels of IL-6 have been found in the airways of infants with RSV bronchiolitis (18,19), and a number of studies have identified IL-17 in the airways (20)(21)(22)(23)(24) and plasma (21,24) of infants with RSV infection. Two studies have found lower levels of IL-17 in the airways of the most severely affected infants, and the authors suggested that higher IL-17 levels were associated with protection against more severe disease (21,24).…”
mentioning
confidence: 99%
“…18 More recently, the investigation into cellular immunity as a whole includes studies on the levels of different interleukins in airway secretions. 16,17,[20][21][22] In an attempt to understand the complex role of IL-2 in immune response, we measured the levels of this cytokine in our study. Our aim was to test out the hypothesis that IL-2 was elevated in the airway secretions of patients with RSV bronchiolitis with indication for hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in the levels of IL-2, IL-6, IL-8, IL-10 have been reported, but some other authors could not observe an increase in the level of some of these cytokines. 16,17,[20][21][22] More specifically, Th1 immune response, through the production of IL-2 and interferon-gamma, has aroused the interest of researchers. However, discrepant results have been found, such as those suggesting that IL-2 is an appropriate means of determining inflammatory response in patients with severe AVB, in the acute phase of the disease, whereas other authors could not observe Th1 immune response, as measured by interferon-gamma, at any stage of the disease.…”
Section: Introductionmentioning
confidence: 99%